The Plasmodium falciparum ABC transporter ABCI3 confers parasite strain-dependent pleiotropic antimalarial drug resistance. Issue 5 (19th May 2022) - Murithi, James M.; Deni, Ioanna; Pasaje, Charisse Flerida A.; Okombo, John; Bridgford, Jessica L.; Gnädig, Nina F.; Edwards, Rachel L.; Yeo, Tomas; Mok, Sachel; Burkhard, Anna Y.; Coburn-Flynn, Olivia; Istvan, Eva S.; et al.
Summary: Widespread Plasmodium falciparum resistance to first-line antimalarials underscores the vital need to develop compounds with novel modes of action and identify new druggable targets. Here, we profile five compounds that potently inhibit P . falciparum asexual blood stages. Resistance selection studies with three carboxamide-containing compounds, confirmed by gene editing and conditional knockdowns, identify point mutations in the parasite transporter ABCI3 as the primary mediator of resistance. Selection studies with imidazopyridine or quinoline-carboxamide compounds also yield changes in ABCI3, this time through gene amplification. Imidazopyridine mode of action is attributed to inhibition of heme detoxification, as evidenced by cellular accumulation and heme fractionation assays. For the copy-number variation-selecting imidazopyridine and quinoline-carboxamide compounds, we find that resistance, manifesting as a biphasic concentration-response curve, can independently be mediated by mutations in the chloroquine resistance transporter PfCRT. These studies reveal the interconnectedness of P . falciparum transporters in overcoming drug pressure in different parasite strains. Graphical abstract: Highlights: P . falciparum ABCI3 is a pleiotropic mediator of antiplasmodial drug resistance Strain-specific resistance was attributed to abci3 amplification or mutant pfcrt Conditional knockdown assays identified ABCI3 as a putative drug target Abstract : Murithi et al. describe ABCI3, an ATP-binding cassette transporter that conveys Plasmodium falciparum resistance to chemically diverse antiplasmodial compounds. In vitro resistance selections, gene editing, drug susceptibility, conditional knockdown, drug cellular accumulation, protein localization, and heme fractionation assays identified ABCI3 as both a resistance mediator and putative drug target.